2014
DOI: 10.1002/adfm.201401244
|View full text |Cite
|
Sign up to set email alerts
|

Tetradentate Platinum Complexes for Efficient and Stable Excimer‐Based White OLEDs

Abstract: wileyonlinelibrary.comlayers, or through the combination of fl uorescent and phosphorescent materials. [9][10][11] With these structures, typically employing iridium complexes, WOLEDs have achieved external quantum effi ciencies over 20%, color rendering index (CRI) over 80, and power effi ciencies over 100 lm/W when advanced outcoupling techniques are employing. [ 12 ] However, the strategy of using multiple emissive materials depends on the precise control over various energy transfer processes within the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 68 publications
1
108
0
Order By: Relevance
“…86) which can show an intense blue emission in a degassed solution with a peak at 470 nm and a tail extended to the green region (Table 9). 333,334 Blue emitter Pt-Az12 (Fig. As a result, all the green PHOLEDs based on Pt-Az9 to Pt-Az11 exhibit EQE of over 10% with PE exceeding 26 lm W À1 , indicating that Pt-Az9 to Pt-Az11 are superior candidates as triplet emitters for green-emitting PHOLEDs.…”
Section: Azole-based Phosphorescent Emittersmentioning
confidence: 94%
See 2 more Smart Citations
“…86) which can show an intense blue emission in a degassed solution with a peak at 470 nm and a tail extended to the green region (Table 9). 333,334 Blue emitter Pt-Az12 (Fig. As a result, all the green PHOLEDs based on Pt-Az9 to Pt-Az11 exhibit EQE of over 10% with PE exceeding 26 lm W À1 , indicating that Pt-Az9 to Pt-Az11 are superior candidates as triplet emitters for green-emitting PHOLEDs.…”
Section: Azole-based Phosphorescent Emittersmentioning
confidence: 94%
“…Li et al designed a series of novel tetradentate Pt(II) complexes containing imidazole moieties. 333 At a low doping level of 2%, the device based on Pt-Az13 shows primarily green emission (l em = 496 nm) with a remarkably high EQE of 25.7%, a CE of 70.6 cd A À1 and a PE of 57.1 lm W À1 . 87) possesses a very high quantum yield of 0.64 in solution and 0.81 in doped PMMA films (Table 9).…”
Section: Azole-based Phosphorescent Emittersmentioning
confidence: 96%
See 1 more Smart Citation
“…4,4 0 ,4 00 -Tris(carbazol-9-yl)-triphenylamine (TCTA) was applied as the host material. 7,[16][17][18] Pt2 also showed excimer-based emission at a high doping level. The device data are summarized in Table 2.…”
Section: Electroluminescence Propertiesmentioning
confidence: 99%
“…2 Recently platinum(II) complexes bearing rigid tetradentate ligands have emerged as an important class of phosphorescent materials because their rigid structure can reduce the probability of nonemissive decay from ligand-centered excited states ( 3 p-p*) and metal-to-ligand charge-transfer (MLCT) excited states through suppressing the vibration and rotation around metal ions, thus leading to high luminescence efficiency. 7 Our interest in this area is to develop robust phosphorescent Pt(II) complexes supported by benzazole-containing ligands. By employing rigid tetradentate Pt(II) complexes, Li et al demonstrated efficient pure blue OLEDs with an external quantum efficiency (EQE) of 22.7% at 100 cd m À2 and Commission Internationale de L'Eclairage (CIE) coordinates of (0.148, 0.079).…”
Section: Introductionmentioning
confidence: 99%